Efficient HIV-1 transmission from macrophages to T cells across transient virological synapses. - Groot, F; Welsch, S; Sattentau, Q (2008)
Macrophages are reservoirs of HIV-1 infection, proposed to transmit virus to CD4(+) T cells, the primary target of the virus. Here we report that human monocyte-derived macrophages (MDMs) rapidly spread HIV-1 to autologous CD4(+) T cells resulting in productive infection. Transmission takes place across transient adhesive contacts between T cells and MDMs, which have the features of a virological synapse including copolarization of CD4 on the T cell with HIV-1 Gag and Env on the macrophage. We propose that an infected MDM can infect at least one T cell every 6 hours. Since HIV-1-infected macrophages can survive for many weeks, these results highlight the central role played by macrophages in HIV-1 infection and pathogenesis.